Cleaner Production Implementation Using Extended Value Stream Mapping For Enhancing The Sustainability Of Lean Manufacturing - Salleh, Mohd Shukor; Ishak, Anuar; Mohamad, Effendi; Sukarma, Lukman; Mahmood, Azmi B.R.; A Rahman, Muhamad Arfauz; Yahaya, Saifudin Hafiz; Salleh, Mohd Shukor; Sulaiman, Mohd Amri (Penerbit UTeM, 2017)
This paper investigated the measures by Cleaner Production (CP) embedded in the modified VSM technique, i.e., Cleaner Production VSM (CPVSM) to be an effective visualisation technique for Lean and promoted the sustainability at 2 local Small and Medium Enterprises (SME’s) for demonstrating the level to which the CPVSM process can be applied. Our findings showed that the implementation of the CP technique was improved through this CPVSM approach and thus promoted the Lean Manufacturing (LM) sustainability.